Screening of black pepper varieties against anthracnose under nursery conditions: Screening black pepper against anthracnose - Verma, Rajshree; Das, Apurba; Narzary, P R; Sarmah, D K; Boro, R C; Kaman, P K; Sharma, Sanjib (Journal of Spices and Aromatic Crops, 2022)
Pathogen causing anthracnose of black pepper was isolated from symptomatic leaf sample and was identified as Colletotrichum gloeosporioides on the basis of morphological, cultural and molecular characterization. Later, pot culture experiment was conducted in greenhouse (year 2020-21) to determine resistance/susceptibility of seven different black pepper varieties viz., Arakkulamunda, Doddigya, Karimunda, Malligesara, Panniyur-1, Poonjarmunda and Uddagare, against anthracnose in nursery condition. It was observed that no variety was resistant but Karimunda variety was found to be highly tolerant against the disease. Whereas, Poonjarmunda and Panniyur-1 were classified as susceptible and highly susceptible, respectively.